1993
DOI: 10.1159/000158969
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Pharmacology of ATP-Sensitive K<sup>+</sup> Channels: Interactions between Glyburide and K<sup>+</sup> Channel Openers

Abstract: This study in isolated rabbit superior artery (RMA) investigated the interactions between glyburide, a known blocker of vascular ATP-sensitive K+ channels (Katp), and several chemically diverse potassium channel openers (PCOs): minoxidil sulfate (MNXS; 5 µM), pinacidil (1 µM), cromakalim (0.5 µM)and RP-49356 (1 µM;a PCO from Rhône Poulenc). Relaxation time courses for these PCOs were obtained in norepinephrine (NE; 5 µM)-precontracted RMA, and the concentrations of PCOs found to be equipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 9 publications
6
29
1
Order By: Relevance
“…Most fibrates are fairly lipid soluble (Miller and Spence, 1998;Mahley and Bersot, 2006) and thus should reach any potential intracellular cytosolic sites of action rather quickly. However, if like certain other lipophilic agents, fibrates must enter the space between bilayers of cellular membranes and then move laterally to reach delayed sites of action (Meisheri et al, 1993), a delay in their action seems reasonable. A more likely possibility is that, within a matter of hours, gemfibrozil is able to accumulate in arterial tissue up to concentrations that exceed its extracellular level.…”
Section: Effects Of Gemfibrozil On K Ne and Avp Induced Contractionsmentioning
confidence: 99%
“…Most fibrates are fairly lipid soluble (Miller and Spence, 1998;Mahley and Bersot, 2006) and thus should reach any potential intracellular cytosolic sites of action rather quickly. However, if like certain other lipophilic agents, fibrates must enter the space between bilayers of cellular membranes and then move laterally to reach delayed sites of action (Meisheri et al, 1993), a delay in their action seems reasonable. A more likely possibility is that, within a matter of hours, gemfibrozil is able to accumulate in arterial tissue up to concentrations that exceed its extracellular level.…”
Section: Effects Of Gemfibrozil On K Ne and Avp Induced Contractionsmentioning
confidence: 99%
“…13,14 However, glibenclamide did not affect the basal tension as well as membrane potential of the omental artery, indicating that ATP-sensitive K ϩ channels may not play a role in the resting tone of visceral circulation in humans. In contrast to this finding, a recent human study has documented that direct administration of glibenclamide to the large coronary artery provokes reduction of resting vessel diameter, suggesting that these channels may modulate resting tone of the large coronary artery in humans.…”
Section: Discussionmentioning
confidence: 93%
“…In vascular smooth muscle cells, this has been extensively stud ied by investigating the interaction between sulpho nylurea derivatives and K vn,-channel-opening drugs [19]. Potassium-channel-opening drugs comprise a group of vasodilator substances, including experi mental therapeutics such as cromakalini.…”
Section: A T P -D E P E N D E N T P O Ta Ssiu M Channels In the Cardimentioning
confidence: 99%
“…First, the glibenclamide concentrations as mentioned above concern peak levels, which of course will persist only for short periods after drug administration. Moreover, the con centrations which were shown to be effective in blocking vascular K ATP-channels [19] are not neces sarily high enough to interact with the more impor tant myocardial KAXP-channels. In this respect it has to be emphasized that differences in the pharmacoki netics between the several sulphonylurea derivatives have to be taken into account since agents with a rel atively short half-life are expected to show shorter periods of high plasma levels as compared with agents which have much longer half- In contrast to the aforem entioned observations, several investigators have shown beneficial effects of glibenclamide during myocardial ischaemia as far as the occurrence of ventricular fibrillation is con cerned.…”
Section: Yocardial Ischaemia and Sulphonylurea Derivativesmentioning
confidence: 99%
See 1 more Smart Citation